A Theology of Forgiveness Theosis in Matthew 18:15–35 - Kim, Kangil (2022)
Jesus’s discussion of the discipline of the church (Matt 18:15-35) shows an example of theosis. While there has been growing interest in theosis among NT scholars, little work has been done on theosis in Matthew’s Gospel. Moreover, scholars who do recognize theosis in Matthew’s Gospel do not attend to how God and the human are united. This article seeks to fill the lacuna. The purpose of this study is to offer a theological exegesis of forgiveness in Jesus’s church discipline. I aim to demonstrate that forgiveness as an embodied way of life is a hermeneutical key to theosis, namely, our transformative participation in God’s life. Forgiveness as an embodied way of life requires the cultivation of particular practices, such as prayer and repentance. This study shows that embodying forgiveness through the practices of prayer and repentance is to take part in the nature and will of the Father in heaven who desires love and mercy (7:21; 12:50; 18:19, 35).
Keywords: Father; Matthew; "kingdom ethics"; Forgiveness; Prayer; Repentance; Theosis; Unity